2015
DOI: 10.1177/1363459314567789
|View full text |Cite
|
Sign up to set email alerts
|

Care pathways as boundary objects between primary and secondary care: Experiences from Norwegian home care services

Abstract: The need for integration of healthcare services and collaboration across organisational boundaries is highlighted as a major challenge within healthcare in many countries. Care pathways are often presented as a solution to this challenge. In this article, we study a project of developing, introducing and using a care pathway across healthcare levels focusing on older home-dwelling patients in need of home care services after hospital discharge. In so doing, we use the concept of boundary object, as described b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 26 publications
3
45
0
Order By: Relevance
“…Coordination technologies apply evidence‐based guidelines to the organization of care for specific conditions in order to improve quality and safety. We included three papers on coordination technologies (see Table 1): a systematic review of the effectiveness of integrated care pathways, 89 qualitative research of a care pathway to integrate primary and secondary care, 90 and a historical account and policy analysis of “chains of care.” 6 …”
Section: Resultsmentioning
confidence: 99%
“…Coordination technologies apply evidence‐based guidelines to the organization of care for specific conditions in order to improve quality and safety. We included three papers on coordination technologies (see Table 1): a systematic review of the effectiveness of integrated care pathways, 89 qualitative research of a care pathway to integrate primary and secondary care, 90 and a historical account and policy analysis of “chains of care.” 6 …”
Section: Resultsmentioning
confidence: 99%
“…According to Gawande (), checklists must be designed to turn on individuals’ brains, not turn them off. However, considering that using well‐designed checklists enables nurses to adhere to more evidence‐based approaches (Laurence & Lynn, ) and use language with increased precision to communicate (Haaland et al, ), the checklists could also represent a supplement to their professional competence and clinical glance. Further efforts to develop checklists should be aware of these precautions to ensure that staff maintain or increase their professional competence and independence.…”
Section: Discussionmentioning
confidence: 99%
“…However, considering that using well-designed checklists enables nurses to adhere to more evidence-based approaches (Laurence & Lynn, 2013) and use language with increased precision to communicate (Haaland et al, 2015), the checklists could also represent a supplement to their professional competence and clinical glance.…”
Section: Pros and Cons Of Checklists In Usementioning
confidence: 99%
“…Previous research on patient involvement in transitional care has revealed that older patients experience a lack of participation during transitions [8][9][10][11]. Transitional care is also characterized by the challenges of coordinating care across organizational and disciplinary boundaries, managing conflicting goals of care, which may be stressful for health care providers (HCPs) [12][13][14]. Dyrstad et al [8] found that the focus on efficiency and time constraints affected patient involvement negatively, and practices were often task-oriented instead of patientoriented.…”
Section: Introductionmentioning
confidence: 99%